Ohmic heating polyphenolic extracts from vine pruning residue with enhanced biological activity - Jesus, Meirielly Santos (2020)
Vine Pruning residue was submitted to conventional heating and ohmic heating (OH) for the extraction of bioactive compounds and analyzed for total phenolic content (TPC), polyphenolic profile, antioxidant activity, antimicrobial activity and anticancer activity. The OH extracts were obtained using Low electric field (496.0 V/cm) or Intermediate electric field - IEF (840.0 V/cm). The tests were performed using 45 % (v/v) ethanol-water extraction solution at 80 °C at different extraction times (20 to 90 min). The extract that stood out among the others concerning anticancer potential was the one obtained by OH when used, IEF, where the TPC was significantly higher than in the other extracts which correlated with higher antioxidant, antimicrobial and anti-proliferative activity on different tumor cell lines (HepG2, MDA-MB-231, MCF-7 and Caco2). Vine pruning OH extracts obtained using green solvents by an eco-friendly procedure were revealed as a source of compounds with relevant antioxidant and anticancer activity.